Eksperimen Penerapan Pembelajaran Matematika dengan Model Student Teams Achievement Division (STAD) dan Jigsaw Terhadap Prestasi Belajar Ditinjau dari Minat Belajar Siswa Kelas VII Semester Genap SMP Muhammadiyah 4 Surakarta Tahun 2015/2016 - Nurjannah, Evi, dris Harta, M.A, Ph. D (2016)
The research is conducted to know: (1) the significant effect of learning model Student Teams Achievement Division (STAD) and Jigsaw to learning achievement of mathematics, (2) the significant effect of learning interest to learning achievement of mathematics, (3) interaction between of learning model Student Teams Achievement Division (STAD) and Jigsaw and learning interest to learning achievement of mathematics. The research is a quasi-experimental research. The population of research is all of the 7th grades of Junior High School in Muhammadiyah 4 Surakarta in academic years of 2015/2016. There are two classes used as sampling is class VIIB and VIIC. The technique of sampling is random sampling. The technique of collection data are test, questionnaire, and documentation. Technique of analyzing data used analysis of variance two different cells. The research result show that: (1) there is significant effect of learning model Student Teams Achievement Division (STAD) and Jigsaw to learning achievement of mathematics i.e. FA=4.700>Ftabel=4.07, (2) there is a significant effect of learning interest to learning achievement of mathematics i.e. FB=4.196>Ftabel=3.22, (3) there is no interaction between learning model of Student Teams Achievement Division (STAD) and Jigsaw and learning interest to learning achievement of mathematics i.e. FAB =1.116 < Ftabel = 3.22.